EVALUASI KUALITAS SKRIPSI DI JURUSAN PAI FITK IAIN SURAKARTA - Purwanto Purwanto (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
This study aimed to start an effort to evaluate the quality of thesis institutionally. The purpose of this study is to determine the quality of the thesis and determine the achievement of the quality of the thesis as a research work. This study is a descriptive evaluation. The study was conducted at the Department of PAI FITK IAIN Surakarta. The results showed several things. First, the majority of PAI student thesis in 2012 used qualitative research methods. Second, the quality of PAI student thesis in 2012 were generally good, on the thesis that uses quantitative and qualitative research methods. Third, the thesis uses quantitative research methods have a higher quality index than the thesis that uses qualitative research methods. Fourth, for the thesis used quantitative research methods showing the low quality of the elements present in the background of the problem and framework of thinking. Fifth, for the thesis used qualitative research methods showing the low quality of the elements contained in the title of the study andbackground of the problem